CREDIT RISK LEVEL ANALYSIS IN PT. BANK SULSELBAR - Bakhitah Hany Putri; Amiruddin Tawe, Nurman, Anwar Ramli, Ahmad Ali (ADISAM Publisher, 2022)
This study aims to determine and analyze the level of credit risk in terms of Non-Performing Loans (NPL) and Loan to Deposit Ratio (LDR) at PT. South Sulawesi Bank. The type of research used is descriptive quantitative. The population in this study is the financial statements of PT Bank Sulselbar from 2016-2020. While the sample in this study is the balance sheet and credit collectibility of PT Bank Sulselbar in 2016-2020. Data analysis techniques using the ratio of Non-Performing Loans (NPL) and Loan to Deposit Ratio (LDR). The results showed that the Non Performing Loan (NPL) of PT. Bank Sulselbar has met the standards set by Bank Indonesia and is included in the safe category because it does not exceed the predetermined limit. In such circumstances PT. Bank Sulselbar is said to be healthy. Loan to Deposit Ratio (LDR) PT. Bank Sulselbar has not met the standards set by Bank Indonesia, because the LDR value of PT. Bank Sulselbar which has exceeded the safe limit. This is PT. Bank Sulselbar is in the unhealthy category and it also shows that the bank's liquidity condition is in a less effective condition.